STRATEGI KEPEMIMPINAN SERIKAT BURUH SEJAHTERA INDONESIA BATAM DALAM MENCIPTAKAN HARMONISASI INDUSTRI KOTA BATAM - Nasruji; Indra Firdiyansyah; Hazriyanto; Andri Hanico (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The leadership of Serikat Buruh Sejahtera Indonesia (SBSI) association has aims to provide the ability to influence with wise communication and motivate others to do something in order to fulfill a common goal which includes the process of assuming as like  recommendation in the organization that has consistent power for reaching the achievement. Geographically, Batam City has great potential in the formation of the SBSI association supported by the existence of companies that was opened and also how the democratic power will giving protection of workers' rights and interests. This study uses qualitative research with a descriptive approach that finds field facts that the SBSI Leadership of Batam City can fulfill the establishment of a harmonization relationship with the company organized in one container, namely  Asosiasi Pengusaha Indonesia (APINDO), active communication can be built by ongoing basis